(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
The interest of scientists, psychiatry and related sciences in disorders of the autism spectrum in children remains relevant. Derived from understanding childhood autism as a major disorder, autism is today seen as a disorder of mental development. Currently, the focus of specialists is not the manifestation of a lack of individual mental abilities of a child with a disorder of the autism spectrum, but the General Laws of disorders in the development of forms of his interaction with the outside world and, above all, with a close person.